AgeWell.de (Germany): World‐Wide FINGERS network: The first global network of multidomain dementia prevention trials. (7th December 2020) - Roehr, Susanne; Hoffmann, Wolfgang; Thyrian, Jochen René; Kaduszkiewicz, Hanna; Frese, Thomas; Gensichen, Jochen; Haefeli, Walter E.; Czock, David; König, Hans‐Helmut; Wiese, Birgitt; Riedel‐Heller, Steffi G.
Abstract: Background: Based on the share of the population aged 65 years and older, Germany is among the world's oldest countries. Therefore, dementia prevention is a very important public health target. AgeWell.de is the first large‐scale multi‐component lifestyle intervention trial against cognitive decline in Germany. It has been designed with a specific focus on a pragmatic approach to allow easy translation into routine care. Method: AgeWell.de is an ongoing multi‐centric, cluster‐randomized controlled multi‐component lifestyle intervention trial aiming at preventing or delaying cognitive decline. Participants are older community‐dwelling general practitioner (GP) patients (60–77 years; n > 1, 000) with increased dementia risk according to the CAIDE (Cardiovascular Risk Factors, Aging, and Incidence of Dementia) dementia risk score. The multi‐component intervention A includes nutritional counseling, physical activity, cognitive training, optimization of medication, management of vascular risk factors, social activity, and, if necessary, further specific interventions targeting grief and depression. Intervention B includes general health advice regarding the intervention components and GP treatment as usual. The observation period is two years. Trained study nurses conduct structured interviews including a comprehensive neuropsychological test battery at baseline and follow‐ups, complemented by motivational telephone sessions with the intervention group. Results: Recruitment and baseline assessments have been completed. Baseline characteristics of the study sample will be presented at AAIC. Conclusion: AgeWell.de covers a broad set of lifestyle interventions. We therefore hope to add additional knowledge on how to effectively shape dementia prevention programs in the future.